2005
DOI: 10.1021/ol050821e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New ChiralN,N,N-Tridentate Pyridinebisimidazoline Ligand Library and Its Application in Ru-Catalyzed Asymmetric Epoxidation

Abstract: A small ligand library of chiral tridentate N,N,N-pyridinebisimidazolines have been synthesized for the first time. This new class of ligands can be easily tuned and synthesized on multi g-scale. The usefulness of the ligands is shown in the ruthenium-catalyzed asymmetric epoxidation with hydrogen peroxide as oxidant. Excellent yields (>99%) and good enantioselectivities (up to 71% ee) have been obtained for the epoxidation of aromatic olefins. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(51 citation statements)
references
References 31 publications
0
44
0
1
Order By: Relevance
“…After stirring the mixture for 2 h at room temperature and filtration of the precipitate the solvent is evaporated. The crude product is crystallized from ethanol/hexane (1) or THF/hexane (2). General procedure for the synthesis of 9 and 10 A suspension of 1 equiv.…”
Section: Discussionmentioning
confidence: 99%
“…After stirring the mixture for 2 h at room temperature and filtration of the precipitate the solvent is evaporated. The crude product is crystallized from ethanol/hexane (1) or THF/hexane (2). General procedure for the synthesis of 9 and 10 A suspension of 1 equiv.…”
Section: Discussionmentioning
confidence: 99%
“…+ salts bearing the (S)-valinol-and (S)-phenylglycinol-derived ligands, 10ae' and 10ba', with PF 6 , SbF 6 or BF 4 counterions, were prepared by standard methodology. These salts were generally obtained as white or yellowish powders, and some of them appeared impure by 1 H NMR analysis.…”
Section: Different (Allyl)-and (13-diphenylallyl)pdmentioning
confidence: 99%
“…[17] It was therein shown that terpyridine binds the (h 1 -allyl)Pd + fragment in the terdentate fashion and (h 3 -allyl)Pd + as a bidentate ligand. In fact, the two species are present both in the crystal and in a CD 2 Cl 2 solution in a dynamic equilibrium, which is strongly displaced towards the h 4 ] adopts the terdentate coordination mode both in the crystal and in solution, where the complex is fluxional through h 1 -h 3 equilibrium processes. [18,19] This is in contrast to the behaviour of (N,P,N) ligands which act as (P,N)-bidentate ligands in (h 3 -dimethylallyl)Pd + complexes.…”
Section: -Allyl) (Nn)pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral imidazolines have been used in a number of applications in asymmetric synthesis [33], among which bidentate phosphine imidazolines have been used in the enantioselective hydrogenation of olefins [34] and allylic substitutions [35], tridentate benzene-bis(imidazolinyl) palladium complexes in asymmetric aza-Morita-Baylis-Hillman reactions [36] and Friedel-Crafts alkylations [37], and pyridinebisimidazoline NNN ligands in ATH [38], asymmetric epoxidation [39] and Henry reactions [40]. Herein, we report the synthesis of Ru(II) complexes bearing a tridentate NNN ligand containing benzimidazolyl and imidazolinyl moieties.…”
Section: Introductionmentioning
confidence: 99%